1986
DOI: 10.7164/antibiotics.39.230
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic .BETA.-lactam antibiotics. I. Synthesis and antibacterial activity of new ureidopenicillin derivatives having catechol moieties.

Abstract: The synthesis and antibacterial activity of new ureidopenicillin derivatives having catechol moieties in the 6-acyl side chain are described. These compounds showed remarkably strong VOL. XXXIX NO. 2 THE JOURNAL OF ANTIBIOTICS 231

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…These data suggested that the full expression of iron-regulated outer membrane proteins is important for in vivo growth. DISCUSSION Recently, ureidopenicillins having a terminal catechol moiety were synthesized and found to have 30-to 60-fold increase in activity relative to piperacillin against various microbes, including Pseudomonas aermginosa strains, which are generally less susceptible to 1-lactam antibiotics (44,46).…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that the full expression of iron-regulated outer membrane proteins is important for in vivo growth. DISCUSSION Recently, ureidopenicillins having a terminal catechol moiety were synthesized and found to have 30-to 60-fold increase in activity relative to piperacillin against various microbes, including Pseudomonas aermginosa strains, which are generally less susceptible to 1-lactam antibiotics (44,46).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Escherichia coli, for example, is known to have at least seven outer membrane proteins whose production is regulated by the availability of ferric iron in the environment; four of them, the products of the fepA, fecA, fluA, and AhuE genes, have been identified as the receptors for ferric enterobactin, ferric citrate, fermchrome, and coprogen, respectively (12,22). Recently, several P-lactam compounds with attached iron-chelating moieties have been developed (9,18,24). Moreover, evidence suggestive of the utilization of a siderophore receptor for outer membrane penetration was obtained for at least one of these compounds, E0702, because E. coli became resistant to this compound if it had tonB mutations, which abolish the transport of all known siderophores as well as vitamin B12 across the outer membrane (26).…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17] Through the tonB dependent iron transport mechanism, 18) the use of catechol substituted b-lactams was known to increase the drug's penetration into the bacterial cell walls. Thus, several catechol-substituted blactams have been synthesized and showed good antimicrobial activities.…”
mentioning
confidence: 99%